Wealth inequality and social mobility: A simulation-based modelling approach - Xiaoliang Yang; Peng Zhou (Cardiff University, Cardiff Business School, 2022)
We design a series of simulation-based thought experiments to deductively evaluate the causal effects of various factors on wealth inequality (the distribution) and social mobility (dynamics of the distribution). We find that uncertainty per se can lead to a 'natural' degree of inequality and returns-related factors contribute more than earnings-related factors. Based on these identified factors, we construct an empirical, hybrid agent-based model to match the observed wealth inequality measures of the G7 countries and China. The estimated model can generate a power-law wealth distribution for the rich and a positively sloped intra-generational Great Gatsby curve. We also demonstrate how this hybrid model can be extended to a wide range of questions such as redistributive effects of tax and finance.
Keywords: D31; E21; J60; 330; Wealth Inequality; Social Mobility; Agent-Based Model